Biología reproductiva de Pseudoplatystoma punctifer (Castelnau, 1855) ¨doncella¨ Y Pseudoplatystoma tigrinum (Valenciennes, 1840) ¨tigre zungaro¨, en San Pablo de Loreto, Río Amazonas, Loreto-Perú - Macedo Mendoza, Sergio Fernando (2023)
The present work had the purpose of knowing the reproductive biology of Pseudoplatystoma punctifer (Castelnau, 1855) ¨doncella¨ and Pseudoplatystoma tigrinum (Valenciennes, 1840) “Tigre zungaro”, in the lower Amazon river basin during the period from November 2020 to October 2021. The specimens came mainly from the Santa Rosa private market, which in turn functions as a landing port in the town of San Pablo de Loreto. A total of 330 Pseudoplatystoma punctifer and 225 Pseudoplatystoma tigrinum specimens were examined. The samples were processed in a market space, implemented with dissection and biometric instruments. Biometric data (lengths and weights) were taken for both species, likewise the identification of gonad maturation was performed by direct observation. The size of first sexual maturity for Pseudoplatystoma punctifer was established at 62.2 cm standard length for females and 47.3 cm for males, and for Pseudoplatystoma tigrinum in 51.8 cm of standard length for females and 40.5 cm for males. The Gonadosomatic Index of Pseudoplatystoma punctifer and tigrinum, has a direct relationship (ρ = 0.308 (females), ρ = 0.186 (males); (ρ = 0.217 (females), ρ = 0.230 (males)) with the variation of the water level of the Amazon River. The sex ratio was defined for Pseudoplatystoma punctifer with 177 (53.60%) female specimens and 153 (46.20%) males representing a sex ratio of 1:1, and for Pseudoplatystoma tigrinum with 109 (48.40%) females and 116 (51.60%) males representing a sex ratio of 1:1, the relationship was not significant in both cases. It is concluded that both species reach their sexual maturity at small sizes, perhaps as a result of the fishing pressure in this area.